Effect of foliar application of Humic acid and Nano Iron on Physical Characteristics of Eggplant (Solanum melongena L.) - Anwar RADHI; Nazar AL GHASHEEM (University of Thi-Qar Journal of agricultural research, 2025)
This experiment was conducted at the open-air researches station of the College of Agriculture and Marshlands, University of Thi Qar, Thi Qar Governorate, Iraq, during 2024-2025. The purpose of the study was to investigate the effect of foliar spraying with humic acid at three concentrations (0, 2, and 4) g/L and foliar spraying with nano-iron at five concentrations (0, 20, 40, 60, and 100) mg/L on the physical characteristics of eggplant (Solanum melongena L. Var. Barcelona). Results showed that (4) g/L Humic acid concentration was superior in terms: Plant height (73.89) cm/plant, leaves number(57.78) leaf), stem diameter(2.67) cm/plant, branches number(3.99) branch/plant, fruits number(19.69)  fruit/plant and fruit weight (118.14) g/fruit. Also, Results showed that (60) mg/L nano-iron concentration was superior in terms (Plant height(73.40)cm/plant, leaves number(53.92) leaf/plant, stem diameter(2.72)cm/plant, branches number(3.74) branches/plant, fruits number(19.31)  fruit/plant and fruit weight (117.69) g/fruit.